Self-Assembled Tamoxifen-Selective Fluorescent Nanomaterials Driven by Molecular Structural Similarity - Park, Jung Yeon; Kim, Jehan; Ha, Jeong Sook; Kim, Yongju (American Chemical Society, 2024)
Most supramolecular systems were discovered by using a trial-and-error approach, leading to numerous synthetic efforts to obtain optimal supramolecular building blocks for selective guest encapsulation. Here, we report a simple coassembly strategy for preparing tamoxifen-selective supramolecular nanomaterials in an aqueous solution. The synthetic amphiphile molecule, 1,1,2,2-tetraphenylethylene (TPE), promotes large tamoxifen aggregate disassembly into smaller, discrete aggregates such as ribbon-like and micellar assemblies in coassembled solutions, enhancing the solubility and dispersion. The TPE moiety exhibits enhanced emission upon tamoxifen interaction, enabling the observation of the coassembled species in an aqueous solution for cell imaging. The tamoxifen-selective fluorescent micelles in the presence of a 1:1 molar ratio of TPE derivative with tamoxifen show enhanced tamoxifen absorption and anticancer effects against MCF-7 breast cancer cells. These supramolecular approaches, based on the coassembly of building blocks with molecular structural similarity, can provide a novel strategy for the efficient development of selective molecular carriers with enhanced biological activities.